Auditoría de gestión aplicada a los procesos de crédito y cobranza y su incidencia en la rentabilidad de la Cooperativa SAC Píllaro de la ciudad de Guaranda, periodo 2023. - Paucar Chisag, Edwin Patricio (2024)
The research “Management audit applied to credit and collection processes and its impact on the profitability of the SAC Píllaro Savings and Credit Cooperative of the city of Guaranda, period 2023” was carried out with the objective of developing the management audit through their respective phases to the credit and collection processes and their impact on the profitability of the Savings and Credit Cooperative Cooperativa de Ahorro y Crédito SAC Píllaro Ltda., of the city of Guaranda in the period 2023, this research was considered descriptive. and field with a mixed approach, that is, both quantitative and qualitative, the information collection techniques were, interview, survey, observation and documentary review, the information collected allowed us to establish that the audit is considered a highly valuable tool. importance that allows the identification and correction of weaknesses of the financial institution, for which a management audit of the credit and collection processes is carried out, with which multiple findings have been determined such as the lack of training, concentration of functions, which can reach To cause bottlenecks, the processes described in the credit manual are not defined in the function flowchart, which is why it has been recommended to schedule continuous training, update the manuals, assign responsibilities, as well as the determination of a new process flowchart.